2D Nanomaterials for Cancer Theranostic Applications. Issue 13 (28th July 2019) - Cheng, Liang; Wang, Xianwen; Gong, Fei; Liu, Teng; Liu, Zhuang
Abstract: 2D nanomaterials with unique nanosheet structures, large surface areas, and extraordinary physicochemical properties have attracted tremendous interest. In the area of nanomedicine, research on graphene and its derivatives for diverse biomedical applications began as early as 2008. Since then, many other types of 2D nanomaterials, including transition metal dichalcogenides, transition metal carbides, nitrides and carbonitrides, black phosphorus nanosheets, layered double hydroxides, and metal–organic framework nanosheets, have been explored in the area of nanomedicine over the past decade. In particular, a large surface area makes 2D nanomaterials highly efficient drug delivery nanoplatforms. The unique optical and/or X‐ray attenuation properties of 2D nanomaterials can be harnessed for phototherapy or radiotherapy of cancer. Furthermore, by integrating 2D nanomaterials with other functional nanoparticles or utilizing their inherent physical properties, 2D nanomaterials may also be engineered as nanoprobes for multimodal imaging of tumors. 2D nanomaterials have shown substantial potential for cancer theranostics. Herein, the latest progress in the development of 2D nanomaterials for cancer theranostic applications is summarized. Current challenges and future perspectives of 2D nanomaterials applied in nanomedicine are also discussed. Abstract : 2D nanomaterials with their unique nanosheet structure, large surface area, and extraordinary physicochemical properties have attracted tremendous interest for application in many different fields including nanomedicine in recent years. The recent progress in the development of different classes of 2D nanomaterials in biomedicine, especially for cancer theranostic applications, is summarized.